2022
DOI: 10.4018/ijamc.292511
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Machine Learning Algorithms for Stock Price and Stock Index Movement Prediction Using Trend Deterministic Data Prediction

Abstract: This experimental study addresses the problem of predicting the direction of stocks and the movement of stock price indices for three major stocks and stock indices. The proposed approach for processing input data involves the computation of ten technical indicators using stock trading data. The dataset used for the evaluation of all the prediction models consists of 11 years of historical data from January 2007 to December 2017. The study comprises four prediction models which are Long Short-Term Memory, XGBo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
6

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 48 publications
(35 reference statements)
0
1
0
6
Order By: Relevance
“…The study utilized trading data calculated from January 2007 to December 2017, encompassing eleven years, incorporating ten technical indicators. The research findings indicated that the random forest algorithm exhibited superior performance [ 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study utilized trading data calculated from January 2007 to December 2017, encompassing eleven years, incorporating ten technical indicators. The research findings indicated that the random forest algorithm exhibited superior performance [ 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Algunas rutinas de preparación de datos, aunque son muy comunes en la mayoría de los casos, hacen que las colecciones de datos sean más eficientes para el análisis. Entre las acciones más frecuentes, que se aplican a los datos en bruto, están la recuperación, la limpieza, la eliminación de datos inútiles o de registros con valores perdidos, la corrección de datos erróneos, el tratamiento de datos atípicos, la discretización y el almacenamiento de datos [394,395,355,396,397]. Además, uno de los problemas más comunes y ampliamente reportados es la presencia de ruido en los datos de entrada [398,329,396].…”
Section: B Actividades De Preparaciónunclassified
“…Uno de los problemas más recurrentes en el uso de métodos de aprendizaje supervisado es el desequilibrio de instancias dentro de los grupos [394,405]. En general, el análisis de eventos con observaciones desiguales se ha planteado como un problema de clasificación multiclase con datos desbalanceados [406].…”
Section: Equilibrio De Clases Desbalanceadasunclassified
See 2 more Smart Citations